Towards a Meta Ethics of Culture – Halfway to a Theory of Metanorms - Karmasin, M. (Journal of business ethics, 2002)
This article deals with cross-cultural ethics. It discusses the grid-group model and is ethical implications. We try to show how cross-cultural ethics remain possible under this paradigm of ethical relativism. We discuss the theory of discourse and apply it to intercultural communication. Finally we offer some rules for (an ethical) intercultural discourse, which also may be interpreted as metanorms for cross-cultural interaction.